Green synthesis of MgO nanocatalyst by using Ziziphus mauritiana leaves and seeds for biodiesel production; Applied Organometallic Chemistry; Vol. 35, iss. 5 - Syed Saman; Aamna Balouch; Farah Naz Talpur; Ayaz Ali Memon; Mousavi Bibimaryam; Verpoort F. V. K. Frensis Valter Kornelius (2021, 2021)
Title screen